Dampak Kegiatan Sosial Palang Merah Indonesia di MIN 3 Medan - U, Usio; Fitra, Aidil; Tanjung, Cindy Agustiana; Purba, Rifaatur Rasyidah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to analyze the impact of social activities of the Indonesian Red Cross (PMI) at MIN 3 Medan. PMI's social activities include health education, blood donation and first aid training. The method used in this research is a qualitative approach with data collection techniques through interviews, observation and documentation. The research results showed that PMI activities had a significant positive impact on increasing students' health awareness, including knowledge about disease prevention and the importance of blood donation. Additionally, first aid training improves students' skills in handling emergency situations. This social activity also succeeded in building cooperation between PMI and schools, which had an impact on increasing community participation in health programs. On the positive side, there are challenges faced, such as limited resources and lack of parental participation in supporting activities. This research concludes that PMI's social activities at MIN 3 Medan are very useful and need to be improved to expand their reach and impact. Recommendations are provided to strengthen collaboration between PMI, schools and the community in order to improve student health and safety.